PEMBERDAYAAN ARSIP NAGARI MELALUI ARSIP ELEKTRONIK DI NAGARI KAMPUNG BATU DALAM DAN NAGARI SIMPANG TANJUNG NAN IV KEC. DANAU KEMBAR KAB. SOLOK (Universitas Negeri Padang, 2021)
The purpose of the Community Partnership Program (PKM) activity is to improve the ability to manage electronic-based archives at the Nagari Kampung Batu Dalam dan Nagari Simpang Tanjuang Nan IV Kec. Danau Kembar Kab. Solok in overcoming the rapid development of technology lately on the one hand has a positive impact on the smoothness and convenience of humans in carrying out various activities, but on the other hand this development also has an impact, especially in the field of archiving which needs to be anticipated immediately. The development in the field of archives is felt to be very slow when it is related to technological developments that directly or indirectly produce archives that tend to always change. For this reason, archival managers should always be responsive and follow these developments and as much as possible so that they can be used for archiving activities. In this activity, the problem will be resolved thoroughly starting from understanding concepts and carrying out electronic-based archive management practices. Activities carried out in the form of electronic-based archive management training using the basic and practical ARTERI application. The training material is tailored to the needs of the participants in order to answer various archive problems that exist at the nagari guardian office level.